2020
DOI: 10.3390/jcs4030088
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Flexible Three-Phase ZnO-Graphene-Epoxy Electro-Active Thin-Film Nanocomposites: Towards Applications in Wearable Biomedical Devices

Abstract: Perovskite oxides have been used as sensors, actuators, transducers, for sound generation and detection, and also in optical instruments and microscopes. Perovskite halides are currently considered as optoelectronic devices such as solar cells, photodetectors, and radiation detection, but there are major issues with stability, interfacial recombination, and electron/hole mobility. The following work looks into the fabrication of non-toxic ZnO-based lead-free alternatives to perovskite oxides for use as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Additionally, 2D materials with low electrical conductivities such as BN and TMDCs display obvious advantages towards inhibiting the galvanic corrosion of epoxy coatings. biodegradable or biocompatible materials [219,220] and biomedical systems [221,222].…”
Section: Anticorrosive Propertiesmentioning
confidence: 99%
“…Additionally, 2D materials with low electrical conductivities such as BN and TMDCs display obvious advantages towards inhibiting the galvanic corrosion of epoxy coatings. biodegradable or biocompatible materials [219,220] and biomedical systems [221,222].…”
Section: Anticorrosive Propertiesmentioning
confidence: 99%
“…Researches on the thin graphene nanoparticles sheets having large surface area but lesser thickness has revealed that they impart better tensile, flexural strength, morphological and other thermal properties and boosts the performance efficiency of the final composites [194][195][196][197][198][199][200]. Three phase, lead-free, ZnO-graphene-epoxy electroactive nanocomposite thin films has been synthesized to serve as a replacement to toxic perovskite oxides traditionally used in sensors, actuators and biomedical wearable devices [201][202][203]. Graphene has also been used as templates to grow metal oxides on it as described in literature [204][205][206].…”
mentioning
confidence: 99%